Synthesis and characterization of thermo-sensitive graft copolymer of carboxymethyl guar and poly(N-isopropylacrylamide) - Gupta, Nivika R.; Ghute, Pallavi P.; Badiger, Manohar V. (Carbohydrate Polymers, 2011)
Thermo-responsive graft copolymers of carboxymethyl guar [CMG] and semitelechelic poly(N-isopropylacrylamide) [PNIPAm] were synthesized by coupling reaction between them using a water-soluble coupling agent namely, 1-(3-(dimethylamino) propyl)-3-ethyl carbodiimide hydrochloride [EDC]. The incorporation of PNIPAm into CMG was confirmed by FT-IR and NMR spectroscopy. The graft copolymers, CMG-g-PNIPAm showed enhanced viscosity as compared to the unmodified CMG in the semi-dilute regime. Due to the presence of a LCST side chains [PNIPAm], the graft copolymers exhibited thermo-responsive nature with respect to temperature which was investigated using pyrene fluorescence probe studies. Although the thermo-responsive property was observed, the thermo-thickening behavior was not seen in these polymers. The graft copolymers in the semi-dilute regime (C(p) approximate to 10-20 g/L) showed viscoelastic properties and the relaxation time, tau, could be obtained from the crossover of frequency (oh) of storage modulus (G') and loss modulus (G `') in the oscillatory experiments. The activation energy `E(a)' of associations was investigated using the time temperature superpsition (TTS). These thermo-responsive polymers along with the biodegradability of CMG can have potential application as industrial thickening agent. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Carboxymethyl guar; Poly(N-isopropylacrylamide); Thermo-sensitivity and graft copolymer